Young Women do it Better: Sexual Dimorphism in Temporal Discrimination - Williams, Laura Jane; Butler, John S.; Molloy, Anna; McGovern, Eavan; Beiser, Ines; Kimmich, Okka; Quinlivan, Brendan; O’Riordan, Sean; Hutchinson, Michael; Reilly, Richard B. (Frontiers in Neurology, 2015)
The temporal discrimination threshold is the shortest time interval at which two sensory stimuli presented sequentially are detected as asynchronous by the observer. Temporal discrimination thresholds are known to increase with age. Having previously observed shorter thresholds in young women than in men, in this work we sought to sytematically examine the effect of sex and age on temporal discrimination. The aims of this study were to examine, in a large group of men and women aged 20 to 65 years, the distribution of temporal discrimination thresholds with an analysis of the individual participant’s responses, assessing the “point of subjective equality” (PSE) and the “just noticeable difference” (JND). These respectively assess sensitivity and accuracy of an individual’s response. In 175 participants (88 women) aged 20-65 years, temporal discrimination was faster in women than in men under the age of 40 years by a mean of approximately 13ms. However age-related decline in temporal discrimination was three times faster in women so that, in the age group of 40-65 years, the female superiority was reversed. The point of subjective equality showed a similar advantage in younger women and more marked age-related decline in women than men, as the temporal discrimination threshold. Just noticeable difference values declined equally in both sexes showing no sexual dimorphism. This observed sexual dimorphism in temporal discrimination is important for both a) future clinical research assessing disordered mid-brain covert attention in basal-ganglia disorders and b) understanding the biology of this sexual dimorphism which may be genetic or hormonal.